The Smeatonians the Society of Civil Engineers - Watson, Garth (Thomas Telford, 1989)
The history of the Society is traced from its formation in 1771 to bring together engineers 'in a friendly way'. The lives of the founding members are described as well as the growing status of civil engineering. The book includes original documents and letters.